Bioorthogonal Deprotection on the Dendritic Cell Surface for Chemical Control of Antigen Cross‐Presentation1. Issue 19 (17th March 2015) - Pawlak, Joanna B.; Gential, Geoffroy P. P.; Ruckwardt, Tracy J.; Bremmers, Jessica S.; Meeuwenoord, Nico J.; Ossendorp, Ferry A.; Overkleeft, Herman S.; Filippov, Dmitri V.; van Kasteren, Sander I.
Abstract The activation of CD8+ T‐cells requires the uptake of exogenous polypeptide antigens and proteolytic processing of these antigens to octamer or nonamer peptides, which are loaded on MHC‐I complexes and presented to the T‐cell. By using an azide as a bioorthogonal protecting group rather than as a ligation handle, masked antigens were generated—antigens that are not recognized by their cognate T‐cell unless they are deprotected on the cell using a Staudinger reduction.